Estimating Discount Functions with Consumption Choices over the Lifecycle - Laibson, David; Lee, Sean Chanwook; Maxted, Peter; Repetto, Andrea; Tobacman, Jeremy (Review of Financial Studies, 2026)
Abstract We estimate β-δ time preferences and relative risk aversion (RRA) using a lifecycle model including stochastic income, liquid and illiquid assets, credit cards, dependents, Social Security, mortality, and bequests. Preference parameters are identified by cross-tabulating four lifecycle age intervals and four balance sheet moments: the share of households carrying (ie, revolving) credit card debt, average carried credit card debt, average net wealth among households carrying credit card debt, and average net wealth among households not carrying credit card debt. The 16 moments are approximately matched by (MSM) parameter estimates β=0.53, δ=0.99, and RRA = 1.9.